Determinants of consumption intention of Chinese cuisines for foreigners: the mediating role of variety seeking behavior. Issue 2 (9th July 2018) - Xuhui, Wang; Muhammad, Asif; Ayyub, Samia
Abstract : Purpose: The purpose of this study is to explore the factors affecting the consumption intention of Chinese cuisines for the foreigners living in China. The study also explains the role of variety seeking behavior of consumers in the consumption intention of Chinese cuisines. Design/methodology/approach: The quantitative data were obtained using a structured questionnaire that is based on Dalian, Liaoning province, of People's Republic of China. A total of 305 responses were collected, and out of which, 282 were analyzed using structural equation modeling. Findings: The results indicate that food novelty and utilitarian value are better predictors of consumption intention of Chinese cuisines. The food quality is also found to be significant with consumption of Chinese cuisines. The variety seeking behavior of consumers found to mediate the relationship of food quality, food novelty and utilitarian value with consumption intention toward Chinese cuisines. Originality/value: The contribution made by the current study is twofold. First, the value of study lies in identifying the factors that are responsible for food consumption intention of foreigners in China, which is an overlooked area in the previous literature. Second, the study also establishes the role of variety seeking behavior of consumers in consumption intention. The authoritative construct of variety seeking behavior matches well with the context of the current study, as the Chinese cuisine is well renowned in the world for its wide variety. Further, the findings are valuable to the stakeholders of restaurant industry in guiding them on how best they can attract foreign consumers toward local Chinese cuisines.